Environmental Attitudes, Brand Image, and Their Influence on Purchasing Decisions for Environmentally Friendly Packaging Products with Gender Variable - Metekohy, Elisabeth Y; ‎ , Fatimah; ‎ , Darna; ‎ , Aminah (KnE Social Sciences, 2024)
Green marketing as part of the company’s marketing strategy is carried out with an ecofriendly concept. This research aims to analyze the influence of environmental attitude and brand image on purchasing decisions for eco-friendly packaging products, both partially and simultaneously. Gender as a moderating variable is used to see whether different genders have different perspectives in responding to green marketing. The population is Generation Z who live in Jakarta and its surroundings. Non-probability sampling techniques were used with a purposive sampling approach combined with convenience sampling. The number of members were 138 from all population areas, selected by accident or convenience. The analysis technique used is moderated regression analysis (MRA). The results of the analysis show that the environmental attitude variable has a positive and significant effect on the purchasing decision variable. The brand image variable has a positive and significant effect on purchasing decisions. Simultaneously, the environmental attitude and brand image variables had a positive and significant effect on the decision to purchase eco-friendly packaging products. Gender as a moderating variable turns out to significantly increase the influence of environmental attitude and brand image on the decision to purchase eco-friendly packaging products by 2%. Keywords: green marketing, eco-friendly, environmental attitude, brand image